Digital Pedagogical Practices of Generation Z Teachers in Primary Education: A Qualitative Study - Arga Pradana; Achadi Budi Santosa; Dian Hidayati (Al-Qalam Institue, 2026)
This study aims to analyze the digital pedagogical practices of Generation Z teachers in primary education, focusing on how they design, implement, and adapt digital-based learning, as well as the challenges they encounter. A qualitative case study approach was employed, involving five Generation Z teachers. Data were collected through semi-structured interviews, field notes, and documentation, and analyzed using thematic analysis to identify key patterns in instructional design, technology integration, and professional attitudes. The findings reveal that Generation Z teachers actively utilize digital platforms for learning management, assessment, and instructional media, demonstrating creative, flexible, and student-centered approaches. However, challenges remain, including limited infrastructure, unequal access to professional training, and time management constraints. The study implies that effective digital pedagogy among Generation Z teachers is shaped by the integration of pedagogical competence, digital literacy, and adaptive professional attitudes, highlighting the need for continuous support in infrastructure and professional development.